Chelation-assisted C-S activation/cascade heteroannulation of pyridine-2-thione derivatives in Pd-catalyzed cross-coupling reaction with alkynes. Issue 37 (14th September 2017) - Zou, Wenxing; Huang, Zongze; Jiang, Kang; Wu, You; Xue, Yuqing; Suzenet, Franck; Sun, Qi; Guillaumet, Gérald
Abstract: Ortho-chelation assistance was proved to be crucial for the success of the desulfitative Sonogashira cross-coupling reaction of thioamide-type pyridine derivatives and alkynes. Corresponding alkynylated products were obtained with moderate to excellent yields. Thanks to this reaction, furo[3, 2- b ]pyridine and 1 H -pyrrolo[3, 2- b ]pyridine derivatives were synthesized through a one-pot cross-coupling reaction/heteroannulation sequence. Graphical abstract: